Nutritional aspects of children and adolescents with epidermolysis bullosa: literature review - Ana Paula Caio Zidorio; Eliane Said Dutra; Dryelle Oliveira Dias Leão; Izelda Maria Carvalho Costa (Anais Brasileiros de Dermatologia, 2015)
Epidermolysis Bullosa is a genetic disorder that affects mainly the skin, however, all others systems are influenced. The nutritional care of children and adolescents with Epidermolysis Bullosa is a key treatment strategy, since the energy needs are increased due to the disease's metabolism, burdening the immune system and cicatrization process, symptoms caused by the disease hinder the intake and adequate absorption of nutrients, which may result in inadequate growth and development. Because this is a rare disease, there are few professionals who know the characteristics of both the clinical evolution and nutritional and dietary treatments. This literature review discusses the latest knowledge on energy and specific nutrient requirements to the dietary treatment and monitoring of children and adolescents with Epidermolysis Bullosa.